Threads of connectivity: Placemaking as a catalyst for bridging the infrastructure divide along the Voortrekker corridor - Masipa, Xenophen (School of Architecture, Planning and Geomatics, 2024)
Architecture is a craft which requires that the architect constantly and intricately create and negotiate relationships between elements. How do buildings interact with their context? What is the relationship between inside and outside? What is the relationship between materials? Infrastructure systems play a vital role in cities, distributing resources throughout the city to ensure its functionality and continuous development. In the book Points + Lines, Stan Allen describes urban infrastructure as artificial ecologies which manage the flow of energy and resources within the city (Allen, 1999). For artificial ecologies to function sustainably, the systems must be interconnected across different infrastructure silos and embedded within the context. However, infrastructure does not just refer to physical infrastructure but also social infrastructure, so it becomes vital to how these systems are connected. Spatial planning was vital in shaping South Africa's spatial environment and was used by the apartheid regime as connectors and dividers. Today, large segments of the City of Cape Town are still subject to the implications of apartheid spatial planning. Communities were divided into cells reinforced with infrastructure buffers (Watson, 2001); this spatial arrangement promoted vehicular movement, which few could afford, thereby restricting access. Although the Voortrekker Road corridor has an established diverse fabric, the railway infrastructure along the corridor also restricts access for some communities. However, this has led to the development of a network of desire lines in and around the railway corridor. The lack of integration by infrastructure with its immediate context creates an opportunity for architecture to connect the city's divided components. The research is focused on the Voortrekker Road Corridor infrastructure network. The paper seeks to understand how infrastructure networks can become integrated with the use of placemaking to serve surrounding communities better. To do this, the paper will focus on unpacking the spatial structure around infrastructure networks and the components of a sustainable city and the importance of public space. This theory and technology paper is divided into five sections with subsections; the first section introduces the site background and conceptual intent. The following section unpacks the structure of Cape Town by analysing the past and future trajectories and proposals by various academics and practitioners on how the city can be improved. The third section analyses the structure of the Voortrekker Road Corridor. The Fourth section unpack the identified Transport Accessible Precincts. Urban Framework and Architectural intent follow this. The final section unpacks two key technological case studies. Followed by the closing and way forward. Infrastructure systems are crucial to sustainable city development; therefore, connecting with surrounding communities becomes crucial. The aim of the project is to create architecture that promotes connectivity between the fragments around infrastructure.